Critical success factors for sustainably establishing localized groundwater supply systems - Kode, Gavin V. M.; Kanyerere, Thokozani; Pietersen, Kevin (Water international, 2024)
Using an evaluation framework, this paper distils the critical success factors for sustainably establishing localized groundwater supply systems at critical care facilities. The learnings are based on developed and implemented plans to ensure water supply and resilience to critical care facilities to survive the 2017/18 drought in the Western Cape Province of South Africa. The success factors include groundwater, regulatory compliance, system design and cost-benefit considerations. The identified key learnings and critical success factors enable future disaster preparedness planners to implement this strategy to make critical facilities more water resilient for water disasters or disasters that lead to water crises.